Mechanics 1 - Quadling, D. A. (Cambridge : Cambridge University Press, 2000)
Each book covers one syllabus unit (except P2 and P3 which are covered in a combined volume). The syllabus content is arranged in chapters to provide a viable teaching course. Each chapter starts with a list of learning objectives. Mathematical concepts, terminology and notation are explained clearly and carefully. Key results and procedures appear in boxes for easy reference. Stimulating worked examples take a stepby- step approach to problem solving and there are plenty of exercises throughout, as well as revision exercises and practice exam papers.
Introduction Velocity and acceleration Force and motion Vertical motion Resolving forces Friction Motion due to gravity Revision exercise 1 Newton's third law Work, energy and power Potential energy Force as a vector quantity General motion in a straight line Revision exercise 2 Practice examinations Answers Index Table of Contents provided by Publisher. All Rights Reserved.
Includes index.
1
Keywords: Mechanics; Mechanics -- Mathematics; Mechanics -- Mathematics -- Problems, exercises, etc